2014
DOI: 10.2337/dc13-0416
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a Mediator of the Influence of Cardiorespiratory Fitness on Cardiometabolic Risk: A Mediation Analysis

Abstract: OBJECTIVEThe relationship between cardiorespiratory fitness (CRF) and metabolic syndrome (MetS) is well known, although the extent to which body weight may act as a confounder or mediator in this relationship is uncertain. The aim of this study was to examine whether the association between CRF and cardiometabolic risk factors is mediated by BMI. RESEARCH DESIGN AND METHODSA cross-sectional study including 1,158 schoolchildren aged 8-11 years from the province of Cuenca, Spain, was undertaken. We measured heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 45 publications
8
63
1
6
Order By: Relevance
“…Previous mediation analyses performed in children aged 8 to 11 years showed that the association between CRF and CVD risk factors was mediated by BMI in both sexes . Our results are in accordance, showing that 79.5%, 100%, 81.2%, and 55.7% of the total effect of CRF on CVDRF‐I in boys and girls children and adolescents, respectively, were mediated by BMI.…”
Section: Discussionsupporting
confidence: 89%
“…Previous mediation analyses performed in children aged 8 to 11 years showed that the association between CRF and CVD risk factors was mediated by BMI in both sexes . Our results are in accordance, showing that 79.5%, 100%, 81.2%, and 55.7% of the total effect of CRF on CVDRF‐I in boys and girls children and adolescents, respectively, were mediated by BMI.…”
Section: Discussionsupporting
confidence: 89%
“…La capacidad cardiorrespiratoria aumentó significativamente en un 9.80%; importante variación, ya que esta se asocia con un menor riesgo cardiometabóli-co 27 . En estudios de 4 meses de duración con abordaje multidisciplinario, la distancia recorrida en el 6MWT se incrementó un 7.17% 28 .…”
Section: Discussionunclassified
“…Cardiorespiratory fitness (CRF) has been negatively associated with abdominal obesity and also with cardiometabolic risk, although it has been suggested that adiposity could mediate the relationship between CRF and cardiometabolic risk in children and adults . Moreover, although MS and CRF have been associated with cardiometabolic risk, studies assessing the independent role of each one have considered the other component of fitness as a confounder and therefore as a factor to be controlled in multivariate models …”
Section: Introductionmentioning
confidence: 99%